THE GRID AS A VISUAL COMPOSITION TOOL IN MORTON FELDMAN’S MUSIC - BELIBOU, Alexandra; IFTENE, Liviu-Valentin (Studia Universitatis Babes-Bolyai Musica, 2025)
This article examines Morton Feldman’s use of graphic notation, focusing on the grid as both a compositional device and a visual framework. Feldman’s innovative approach reflects his search for a musical language that transcended conventional notation and emphasized sound as an autonomous phenomenon. The evolution of his grids, from early box structures to later flexible forms, illustrates his adaptability and his concern with balancing clarity and openness. By analyzing selected scores, including Intersection 2, and The King of Denmark, the study demonstrates how Feldman’s graphic methods shaped the relationship between composer, performer, and audience.